Relationship of Parenting Style and Teenage¡¦s Delinquency - Novi Cahyaningsih; Dwi Hastuti Martianto; Melly Latifah (Media Gizi dan Keluarga, 2000)
The general objective of the study is to determine relationship between parenting style and teenase delinquency. The study was conducted among senior high school children in Central Jakarta. There were 306 teenagers served as respondents of this study. Results of the study showed that internal reliability of teenage delinquency measurement was 0.9 which indicates that the tools was very good in assessing teenage delinquency. Finding showed is that family characteristics such as fathers educational attainments is negatively correlated to teenage delinquency, while family size is positively correlated to teenage delinquency.Parenting style which is indicated as otoritarian, permissive and democratize also correlated to teenage delinquency. Positive and significant relatinnship (ƒÑ=0.05) was estabilished between permissive parenting style and teenage delinquency. On the other hnad, the democratize parenting style is negative and significantly (ƒÑ=0.01) related to teenage delinquency. Therefore, parents were and encouraged to apply democratize parenting style to help reduce teenage delinquency among senior high school children.